Проблеми використання енергетичного органічного палива та шляхи їх вирішення - Скляренко, Олег Михайлович; Довгалюк, Володимир Борисович; Шишина, Марія Олексіївна; Горбачова, Ярослава Володимирівна (КНУБА, 2018)
Розглянуто проблеми, що пов’язані з динамікою зростання споживання енергетичного палива – дефіцит енергоресурсів і збільшення навантаження на навколишнє середовище шкідливими речовинами продуктів згорання. Аналіз ряду наукових досліджень показує, що зниження вмісту шкідливих речовин (SOx, NOx) в продуктах згорання неможливе без принципових змін в організації топкових процесів. Реалізація цих змін можлива за допомогою переходу на нові принципи спалювання вуглеводнів. Переважну частину теплогенераційного обладнання України складають застарілі та фізично зношені тепло агрегати часів СРСР, у яких рівень вмісту шкідливих речовин та парникових газів у продуктах згорання набагато перевищує гранично допустимі відповідно до екологічних нормативів країн Європейського Союзу. Обґрунтовано необхідність модернізації теплогенеріційного обладнання задля підвищення енергетичної ефективності використання ресурсів та зниження шкідливого впливу на навколишнє середовище. Зменшення впливу шкідливих речовин може бути досягнуто за рахунок енергозбереження і модернізації технологій виробництва. На основі аналізу розвитку енергетики показано, що основними засобами розв’язання цих проблем є реалізація концепцій енергозбереження і енергозаміщення. Також у статті розкрита концепція Національної стратегії з енергозбереження та енергозаміщення традиційних первинних енергоресурсів альтернативними паливними джерелами енергії. The article discusses the problems associated with the dynamics of growth in the consumption of energy fuels – the shortage of energy resources and the growth of the load on the environment by harmful substances, which are contained in the combustion products of fuel. An analysis of a number of scientific studies shows that it is impossible to reduce the content of harmful substances (SOx, NOx) in combustion products without fundamental changes in the organization of furnace processes. The implementation of these changes is possible through the transition to new principles of combustion of hydrocarbons. The predominant part of the heat-generating equipment of Ukraine is made up of outdated and physically worn-out heat units of the USSR, in which the content of harmful substances and greenhouse gases in the combustion products is many times higher than the maximum permissible according to EU environmental standards. The necessity of modernization of heat-producing equipment with the aim of improving the efficiency of combustion of fuel and reducing the negative impact on the environment is substantiated. Reducing the influence of harmful substances can be achieved through energy saving and modernization of production technologies. Based on the analysis of the development of the power industry, it is shown that the main means of solving the above problems is the implementation of the concept of energy saving and energy replacement. The concept of the National Strategy for Energy Saving and Energy Replacement of Traditional Primary Energy Resources with Alternative Sources is also disclosed. It was determined that the main problem in the world energy sector is not a shortage of energy fuel, but a lack of investment in the energy saving of fossil fuel and its energy supply. Formed energy development until 2025 is based on the use of traditional organic fuels and advanced technologies for processing them into electrical and thermal energy. The environmental threat to the development of civilization comes largely from the technological emissions of energy complexes. Reducing the influence of harmful substances can be achieved through energy saving and modernization of production technologies.
Fossil fuel usage issues and ways to deal with
https://doi.org/10.32347/2409-2606.2018.26.56-61
Keywords: органічне паливо; шкідливі викиди; енергоресурси; енергозбереження; енергозаміщення; 620.925:504